Supply Chain Performance Influencer in Construction Domain: A Key Factor Analysis - Kumar, Vivek; V. RAO, Y.; Kumar, Vikash (International Journal of Engineering and Technology, 2018)
In this study the improvement of supply chain process based on the supply chain management has been considered. In this regard,  two vital factor of time and cost  has been  taken into account to optimize the process of product delivery. To harness the available methods, among the all options, the construction company’s integration has been elicited in order to improve the business process by concentrating best logistic and supply chain factors to improve the construction quality and standards.  By ensuing the proposed methods, the importance of supply chain relationships in construction companies as well as efficiency of the flowed information in terms of relevant data to improve customer and supplier relation has been manifested. In the strategies, followed aforementioned trends, the best potential tools for improvement of constructed companies have been identified. At the end, implementing the mentioned strategies, the obtained results attested the quality performance and supply chain management expediency.